RANCANGAN ANTENA MONOPOLE PERALATAN RECEIVER AUTOMATIC DEPENDENT SURVEILLANCE BROADCAST (ADS-B) SEBAGAI ALAT BANTU PEMBELAJARAN DI PROGRAM STUDI TEKNIK TELEKOMUNIKASI DAN NAVIGASI UDARA - Feti Fatonah; Djoni Slamet Hardjono R; I. Gede Made Wahyu Pranata (Langit Biru: Jurnal Ilmiah Aviasi, 2016)
Indonesian Civil Aviation Institute (ICAI) is one college official who is under the Ministry of Transportation. In carrying out its duties and functions, STPI has four educational Training Division, namely: Pilot Training Division, Aviation Engineering Training Division, Aviation Safety and Flight Management Training Division. Aviation Engineering Training Division has five courses, one of which is the Telecommunications Engineering Program and Air Navigation (TNU). Technological developments in the world aviation industry is advancing very rapidly. Recent developments in navigation and communication technology, data link between the aircraft and ground control station are available is the Automatic Dependent Surveillance Broadcast (ADS-B). ADS-B is a way in which aircraft can automatically send or receive data such as identification, position and other data in the form of broadcast (broadcast) via data link. Antenna is one of the important components in every electronic equipment transmitter and receiver. Similarly, in the ADS-B receiver equipment. Determining the type of antenna used must have the same properties as the channel pencatunya. Antennas on ADS-B receiver equipment only as recipients of the signals sent by air from all directions, the antenna used is a type of omnidirectional antenna. ADS-B receiver antenna has a monopole shape, with the working frequency of ADS-B equipment on 1090 MHz. In order to maximize the understanding of cadets and can figure out how to design an antenna that can be applied to the ADS-B receiver equipment, it needs to be made an antenna design that can be used to support the practical activities of cadets. Cadets can practice direct measurement of the antenna and see the antenna radiation pattern using the equipment in the lab Telecommunication Engineering Program and Air Navigation.